Experience Marketing in the Service of the “Secular Religion” of Big Tech - Jan KREFT; Monika BOGUSZEWICZ-KREFT (Communications of International Proceedings, 2021)
The article proposes an interpretation of the meaning of experience marketing as a tool in the process of sacralisation of products, and in a broader context – the so-called secular religion accompanying some contemporary big tech organizations. The article is of theoretical nature and the authors have intended to explain how big tech corporations, in line with the concept of experience marketing (digital platforms, in particular), reinterpret their role in relations with users. The aim of the article is to inspire research on the experience marketing in the digital ecosystem in the context of the sacralisation of an organization, its goals, leaders, employees and products. The article has adopted hermeneutics as providing an appropriate theoretical framework for analysis.
Keywords: Experience Marketing; Platforms; Sacralisation; Sacralised Products; Mythologization